PEMBUATAN BONEKA HORTA SEBAGAI PEMANFAATAN LIMBAH SERBUK KAYU DAN PEMBELAJARAN PERAWATAN TANAMAN DI SDN 2 GUMUKREJO - Noviani, Rita; Fahreza, Zainal Ihza; Handayani, Beta Amanda Putri; Shanti, Uri Ashe; Puwa, Maharani Ladja; Khoirunnissa, Yulia Anggita; Cecilia, Danela Teguh; Andriyani, Yunika; Megasih, Adila; Swastika, Tia; Ramadhan, A’an Nur Khisma (MAJU : Indonesian Journal of Community Empowerment, 2024)
Horta Doll program explores the application of innovative learning methods at SDN 2 Gumukrejo as an effort to cultivate students' environmental awareness and creativity. Horta dolls, which are planting media shaped like dolls made from organic materials with plant seeds inside, are used to introduce the concept of plant growth in a direct and enjoyable way. The demonstration method is applied in this workshop to provide an interactive experience that engages students in creating and caring for Horta dolls. The results show high enthusiasm from students, as well as an increase in environmental awareness and creativity. This environment-based learning proves effective in teaching students about plant growth and care for the environment practically..